Structural dynamics effects on the electronic predissociation of alkyl iodides - Murillo-Sánchez, Marta L. (Sci Rep, 2020)
The correlation between chemical structure and predissociation dynamics has been evaluated for a series of linear and branched alkyl iodides with increasing structural complexity by means of femtosecond time-resolved velocity map imaging experiments following excitation on the second absorption band (B-band) at around 201 nm. The time-resolved images for the iodine fragment are reported and analyzed in order to extract electronic predissociation lifetimes and the temporal evolution of the anisotropy while the experimental results are supported by ab initio calculations of the potential energy curves as a function of the C-I distance. Remarkable similarities are observed for all molecules consistent with a major predissociation of the initially populated bound Rydberg states 6A″ and 7A′ through a crossing with the purely repulsive states 7A″, 8A′ and 8A″ leading to a major R + I*((2)P(1/2)) (R = CH(3), C(2)H(5), n-C(3)H(7), n-C(4)H(9), i-C(3)H(7) and t-C(4)H(9)) dissociation channel. The reported electronic predissociation lifetimes are found to decrease for an increasing size of the linear radical, reflecting the shifts observed in the position of the crossings in the potential energy curves, and very likely a greater non-adiabatic coupling between the initially populated Rydberg states and the repulsive states leading to dissociation induced by other coordinates associated to key vibrational normal modes. The loss of anisotropy is fully accounted for by the parent molecular rotation during predissociation and the rotational temperature of the parent molecule in the molecular beam is reasonably derived.